Гральні набори з розкопок П.І. Смолічева із заплавного могильника Шестовиці - Хамайко, Н.В. (Археологія, 2016)
У статті на підставі архівних матеріалів здійснюється републікація втрачених нині скляних гральних наборів, знайдених під час досліджень П.І. Смолічевим Шестовицького заплавного могильника влітку 1926 р. Based on the archival sources, the republication of lost today gaming pieces found during the research at the floodplain burial ground by P.I. Smolychev in 1926 is conducted in the article. Systematized is the data on the analogies, on the chronology of assemblages and the typological structure of the pieces, which are found in the 10th century burials, and also as single findings in synchronous cultural layers at the settlements in Kyiv Rus and Scandinavia. Gaming pieces made of glass are concentrated in so called «retinue» centres related with the Scandinavian influence and were the imports for Kyiv Rus. Analogies of glass pieces reveal their belonging to North European cultural circle, irrespectively of their place of production, which is not finally determined today. Discoveries of such findings in barrows at Shestovytsia, with a cremated at the place burial among them containing the remains in urn peculiar for the 10th century Slavs in Ancient Rus millieu, testify that the game was adopted by the local population, though with reservation on localization of such findings at the main trade routs. В статье на основании архивных источников осуществляется републикация утраченных в настоящее время игральных фигурок, найденных при исследованиях Шестовицкого пойменного могильника П.И. Смоличевым в 1926 г. Систематизированы данные об аналогиях, хронологии комплексов и видовом составе фигурок, которые обнаруживаются в погребениях Х в., а также в качестве единичных находок в синхронных культурных слоях поселений Древней Руси и Скандинавии. Стеклянные игральные фигурки концентрируются в так называемых «дружинных» центрах, в комплексах, связанных со скандинавским влиянием, и являются импортами для Руси. Независимо от места производства последних (на сегодня до конца не выясненного), аналогии выявляют их принадлежность к североевропейскому культурному кругу. Обнаружение подобных находок в шестовицких курганах, погребение одного из которых совершено по типу кремации на месте с помещением останков в урну, характерному для славян древнерусского ареала в Х в., говорит о заимствовании игры местным населением, хотя и с оговоркой на локализацию подобных находок на больших торговых путях.